Pengembangan Paket Pembelajaran IPS Multi Media dalam Pembelajaran IPS Kelas VIII di MTSN 24 Jakarta - Dzulfikar Akbar; Nurdin Ibrahim; Moch. Sukardjo (Peneliti.net, 2019)
This study aims to produce a product in the form of a multi-media IPS learning package for class VIII students at MTSN 24 Jakarta. The research methodology uses the R & D method. The product testing phase begins with the validation of several experts namely material experts, media experts and instructional design experts. With the acquisition of an average material expert of 3.63 media experts an average of 3.26 and an instructional design expert on average 3.68 means that the multi-media IPS learning package is feasible to use. Furthermore, the product was tested for the number of class VIII students with thetest one to one as many as 3 students obtained an overall average score of 3.82. In conclusion, the social studies learning package developed has been very good and feasible for use in the social studies learning process.